No man's land [videorecording (DVD)] - Allyn, Jake; Allyn, Jake; Grillo, Frank, 1963-; Jimenez, Jorge A. (Actor); MacNicoll, Alex (Shout! Factory, 2021)
While out on a father-son border patrol, Jackson accidentally kills a Mexican immigrant boy. When Jackson's father tries taking the blame, Jackson flees south on horseback, becoming a gringo 'illegal alien' in Mexico. Chased by Texas Rangers and Mexican Federales, Jackson journeys across Mexico to seek forgiveness from the dead boy's father only to fall in love with the land he was taught to hate.